A Study Of Cohesive Devices In News Articles About Ratu Atut In Jawa Pos Newspaper - Anthony Chandra (2014)
This is a study of discourse analysis of types of cohesion devices applied in news article. Cohesive devices focus on the inter-relationship between text based on the grammatical and the lexical structure. The aim of this study is to discover the types of cohesive devices found in the text and which type of cohesive devices is frequently used in the news article text. The subject of this study is the news article in Jawa Pos, which talks about one of the prominent political figures in Indonesia, Ratu Atut. The discourse analysis theory about cohesive devices by Halliday and Hassan (1976), from the grammatical cohesion (reference, substitution, ellipsis, conjunction) and the lexical cohesion (collocation and reiteration), is used to analyze the data and will be supported by Hoey's (1991) lexical cohesion. In conducting the study, the writer uses qualitative approach to gather the data. From this study, it is revealed that all of cohesive devices types are found in the text except for collocation and reference is the most frequently used type of cohesive devices in the text.